A comparison of artificial neural network and extended Kalman filter based sensorless speed estimation - Aydogmus, Zafer; Aydogmus, Omur (Elsevier Sci Ltd, 2015)
In industry speed estimation is one of the most important issue for monitoring and controlling systems. These kind of processes require costly measurement equipment. This issue can be eliminated by designing a sensorless system. In this paper we present a sensorless algorithm to estimate shaft speed of a dc motor for closed-loop control using an Artificial Neural Network (ANN). The method is based on the use of ANN to obtain a convenient correction for improving the calculated model speed. Three architectures of ANNs are developed and performance evaluations of the networks are performed by three performance criteria. After the evaluations, Levenberg-Marquardt backpropagation algorithm is chosen as learning algorithm due to its good performance. The speed estimation performance of developed ANN was compared with Extended Kalman Filter (EKF) under the same conditions. The results indicates that the proposed ANN shows better performance than the EKF. And ANN model can be used for speed estimation with reasonable accuracy. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Speed estimation; Neural networks; Sensorless control; Model-based estimation